A comprehensive genomic analysis provides insights on the high environmental adaptability of Acinetobacter strains - Zhao, Yang; Wei, Hua-Mei; Yuan, Jia-Li; Xu, Lian; Sun, Ji-Quan (Frontiers in Microbiology, 2023)
Acinetobacter is ubiquitous, and it has a high species diversity and a complex evolutionary pattern. To elucidate the mechanism of its high ability to adapt to various environment, 312 genomes of Acinetobacter strains were analyzed using the phylogenomic and comparative genomics methods. It was revealed that the Acinetobacter genus has an open pan-genome and strong genome plasticity. The pan-genome consists of 47,500 genes, with 818 shared by all the genomes of Acinetobacter, while 22,291 are unique genes. Although Acinetobacter strains do not have a complete glycolytic pathway to directly utilize glucose as carbon source, most of them harbored the n-alkane-degrading genes alkB/alkM (97.1% of tested strains) and almA (96.7% of tested strains), which were responsible for medium- and long-chain n-alkane terminal oxidation reaction, respectively. Most Acinetobacter strains also have catA (93.3% of tested strains) and benAB (92.0% of tested strains) genes that can degrade the aromatic compounds catechol and benzoic acid, respectively. These abilities enable the Acinetobacter strains to easily obtain carbon and energy sources from their environment for survival. The Acinetobacter strains can manage osmotic pressure by accumulating potassium and compatible solutes, including betaine, mannitol, trehalose, glutamic acid, and proline. They respond to oxidative stress by synthesizing superoxide dismutase, catalase, disulfide isomerase, and methionine sulfoxide reductase that repair the damage caused by reactive oxygen species. In addition, most Acinetobacter strains contain many efflux pump genes and resistance genes to manage antibiotic stress and can synthesize a variety of secondary metabolites, including arylpolyene, β-lactone and siderophores among others, to adapt to their environment. These genes enable Acinetobacter strains to survive extreme stresses. The genome of each Acinetobacter strain contained different numbers of phages (0–12) and genomic islands (GIs) (6–70), and genes related to antibiotic resistance were found in the GIs. The phylogenetic analysis revealed that the alkM and almA genes have a similar evolutionary position with the core genome, indicating that they may have been acquired by vertical gene transfer from their ancestor, while catA, benA, benB and the antibiotic resistance genes could have been acquired by horizontal gene transfer from the other organisms.